An investigation of the implementation of NICE-recommended CBT interventions for people with schizophrenia. (August 2014) - Haddock, Gillian; Eisner, Emily; Boone, Candice; Davies, Gabriel; Coogan, Catherine; Barrowclough, Christine
Abstract Background: The National Institute for Clinical Excellence (NICE) guidelines recommend that individual cognitive-behaviour therapy (CBT) is offered to all people with a diagnosis of schizophrenia. In addition, the guidelines recommend that family intervention (FI) should be offered to all families of people with schizophrenia who are in close contact with the service user. However, implementation into routine services is poor. Aims: To survey mental health services to investigate how many people with a diagnosis of schizophrenia and their families are offered and receive CBT or FI. Methods: A comprehensive audit of a random sample of 187 service users receiving care from one, large mental health care trust in North West England was conducted over a 12-month period. Results: The audit recorded that only 13 (6.9%) of services users were offered and 10 (5.3%) received individual CBT, while 3 (1.6%) services users were offered and 2 (1.1%) received FIs within the 12-month audit period. Conclusions: Implementation of CBT and FI is poor, particularly for FI. Reasons for poor implementation and service implications are discussed.